Nódulo tiroideo, enfoque y manejo. Revisión de la literatura (2013)
Thyroid nodules are commonly found, and their incidence is increasing. The main objective during the evaluation of these nodules is to determine if they are benign or malignant. Materials and methods: We made a narrative review of the literature by searching Ovid, Medline and Lilacs from 1950 to 2010. Results: Most thyroid nodules are benign, but in 4% to 8% of cases they may be malignant, hence the importance of appropriate study and management. Nodules larger than 1 cm should undergo fine needle aspirate; however, the clinical features of the patient and the characteristics of the nodule on ultrasound assessment should always be taken into account. The following are risk factors associated with the presence of thyroid nodules: age over 45 years, female gender and smoking. The measurement of tumor markers in the initial study of patients with thyroid nodule is not recommended. Conclusion: Ultrasound and thyroid fine needle aspirate are the most important diagnostic methods in the evaluation of thyroid nodules, because they enable to make changes in therapeutic decisions thus decreasing the number of unnecessary thyroidectomies. Treatment and prognosis of thyroid nodules will depend on the patient´s risk factors and the cytological and pathological findings.